2022
DOI: 10.1590/1980-220x-reeusp-2021-0470en
|View full text |Cite
|
Sign up to set email alerts
|

Risk of depression in pregnancy among pregnant women undergoing high-risk prenatal care

Abstract: Objective: to identify the risk of depression in pregnancy among pregnant women undergoing follow-up in high-risk prenatal care, to assess the factors associated with higher risk of depression in pregnancy and to compare the risk of depression in each gestational trimester. Method: this is a descriptive, correlational, cross-sectional study, conducted with 151 pregnant women in prenatal care in a high-risk pregnancy outpatient clinic at a university hospital in the state of São Paulo, Brazil. Data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Of the maternal health variables analyzed in the present study, being in the group with a high-risk pregnancy, that is, having a disease associated with the current pregnancy, did not prove to be a risk factor for depression during pregnancy compared with a low-risk pregnancy. Unlike our findings, other studies ( 43 , 56 , 57 ) indicate that having a disease associated with pregnancy is a risk factor for depression during pregnancy. One of the most relevant aspects related to different results in the present study is the specific characterization of the group with low-risk women, mainly composed of women working in the institution’s own health department, which may generate bias.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of the maternal health variables analyzed in the present study, being in the group with a high-risk pregnancy, that is, having a disease associated with the current pregnancy, did not prove to be a risk factor for depression during pregnancy compared with a low-risk pregnancy. Unlike our findings, other studies ( 43 , 56 , 57 ) indicate that having a disease associated with pregnancy is a risk factor for depression during pregnancy. One of the most relevant aspects related to different results in the present study is the specific characterization of the group with low-risk women, mainly composed of women working in the institution’s own health department, which may generate bias.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this association was not maintained throughout pregnancy. Another study ( 43 ) with pregnant women treated at a university hospital in the city of São Paulo identified that participants with a partner had an 89% lower risk of depression during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the higher risk of depression in the first trimester of pregnancy reiterates the importance of universal screening, as recommended internationally by various organizations such as the American College of Obstetricians and Gynecologists ( 32 ) , the US Preventive Services Task Force ( 33 ) , and the American College of Nurse-Midwives ( 34 ) , but unfortunately not implemented in Brazil. This measure would enable early intervention to prevent the development of depressive disorders, facilitate timely referral of pregnant women to specialized mental health care if necessary, and reduce healthcare costs ( 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some medical problems that lead to NICU admission are diagnosed prenatally (e.g., genetic conditions and cardiac diagnoses), which can contribute to fears about the infant’s development and well-being throughout the pregnancy. High-risk pregnancies are associated with postpartum and post-traumatic stress, depression, and anxiety, and mental health concerns during pregnancy can be compounded by a potentially traumatic birth [ 7 ]. NICU mothers are also more likely to perceive childbirth as traumatic compared to well-baby mothers.…”
Section: Introductionmentioning
confidence: 99%